Spiritualitas Elitis dan Krisis Etika Sosial Kristen dalamFenomena Megachurch di Indonesia - Debby Christ Mondolu (Sekolah Tinggi Alkitab Jember, 2026)
The megachurch phenomenon in Indonesia reflects a shift in modern spirituality that emphasizes grandeur, prosperity, and social status as signs of faith’s success. This trend gives rise to an elitist spirituality that risks obscuring core Christian social ethics such as love, solidarity, and justice. This study aims to analyze the characteristics of elitist spirituality, its impact on the crisis of social ethics within the church, and to offer a theological reflection that restores a faith centered on love and service. Using a qualitative and theological-critical approach through literature review, social observation, and biblical interpretation (Luke 4:18–19; Matthew 25:31-46; Philippians 2:5-11), the study finds that prosperity theology and corporate culture within megachurches equate faith with economic success while neglecting social solidarity. Therefore, the church must reinterpret success through incarnational spirituality modeled on Christ, bringing God’s love and justice back into the heart of society. Fenomena megachurch di Indonesia menunjukkan pergeseran spiritualitas modern yang menonjolkan kemegahan, kemakmuran, dan status sosial sebagai tanda keberhasilan iman. Pola ini melahirkan spiritualitas elitis yang berpotensi mengaburkan nilai etika sosial Kristen seperti kasih, solidaritas, dan keadilan. Penelitian ini bertujuan menganalisis karakteristik spiritualitas elitis, dampaknya terhadap krisis etika sosial gereja, serta menawarkan refleksi teologis untuk memulihkan iman yang berpusat pada kasih dan pelayanan. Dengan pendekatan kualitatif dan analisis teologis-kritis terhadap literatur, fenomena sosial, dan teks Alkitab (Luk. 4:18-19; Mat. 25:31-46; Flp. 2:5-11), ditemukan bahwa teologi kemakmuran dan budaya korporatis dalam megachurch mengidentikkan iman dengan kesuksesan ekonomi dan mengabaikan solidaritas sosial. Gereja karenanya perlu menafsir ulang makna keberhasilan dalam terang spiritualitas inkarnatif yang meneladani Kristus dan menghadirkan kasih serta keadilan Allah di tengah masyarakat.